Record‐Low Arctic Stratospheric Ozone in 2020: MLS Observations of Chemical Processes and Comparisons With Previous Extreme Winters. Issue 16 (17th August 2020) - Manney, Gloria L.; Livesey, Nathaniel J.; Santee, Michelle L.; Froidevaux, Lucien; Lambert, Alyn; Lawrence, Zachary D.; Millán, Luis F.; Neu, Jessica L.; Read, William G.; Schwartz, Michael J.; Fuller, Ryan A.
Abstract: Aura Microwave Limb Sounder (MLS) measurements show that chemical processing was critical to the observed record‐low Arctic stratospheric ozone in spring 2020. The 16‐year MLS record indicates more polar denitrification and dehydration in 2019/2020 than in any Arctic winter except 2015/2016. Chlorine activation and ozone depletion began earlier than in any previously observed winter, with evidence of chemical ozone loss starting in November. Active chlorine then persisted as late into spring as it did in 2011. Empirical estimates suggest maximum chemical ozone losses near 2.8 ppmv by late March in both 2011 and 2020. However, peak chlorine activation, and thus peak ozone loss, occurred at lower altitudes in 2020 than in 2011, leading to the lowest Arctic ozone values ever observed at potential temperature levels from ∼400–480 K, with similar ozone values to those in 2011 at higher levels. Plain Language Summary: Unlike the Antarctic, the Arctic does not usually experience an ozone hole because temperatures are often too high for the chemistry that destroys ozone. In 2019/2020, satellite measurements show record‐low stratospheric wintertime temperatures and record‐low springtime ozone concentrations in the Arctic lower stratosphere (about 12‐ to 20‐km altitude). Only one other winter/spring season, 2010/2011, in this 16‐year satellite data record comes close. Low temperatures, which result in chlorine being converted from nonreactive forms into forms that destroy ozone, started earlier than in any previous Arctic winter in the record and lingered later than in any year except 2011. The ozone‐destroying chemistry in 2019/2020 occurred at lower altitudes (where more of the ozone that filters out harmful ultraviolet radiation resides) than in 2010/2011. Such extensive ozone loss can have important health and biological impacts because it leads to more ultraviolet radiation reaching the Earths surface. While the success of the Montreal Protocol in limiting human emissions that increase ozone‐destroying gases in the stratosphere has resulted in much less Arctic ozone destruction than we would have otherwise had, future temperature changes could lead to other winters with even more chemical ozone depletion than in 2019/2020. Key Points: MLS trace gas data show that exceptional polar vortex conditions led to record‐low ozone in the Arctic lower stratosphere in 2019/2020 Early and persistent cold conditions led to the longest period with chlorine in ozone‐destroying forms in the 16‐year MLS data record Chemical ozone destruction began earlier than in any Arctic winter in the MLS record and ended later than in any year except 2010/2011